News from Tartary : an Epic Journey Across Central Asia. - Fleming, Peter, 1907-1971 (Fleming, Peter, 1907-1971. Peter Fleming collection., 2014)
News from Tartary describes a phenomenally successful attempt that legendary adventurer, Peter Fleming made to travel overland from Peking to Kashmir. The journey took seven months and covered about 3,500 miles. With his companion, adventurer and writer, Ella Maillart, they set out across a China torn by civil war to journey through Xinjiang to British India. It had been eight years since anyone had crossed Xinjiang; in between those who had entered this inhospitable and politically volatile area - under the control of a warlord supported by Stalin''s Red Army - seldom left alive. Entering the.